KAJIAN RETRIBUSI KANTIN DENGAN SKENARIO DI KOTA MALANG TAHUN 2025 - Muhammad Syafiq; Dian Surya Ayu Fatmawati; Ary Yunita Anggraeni; Nofita Tahmer; Cindy Getah Trisna June (KRISNA: Kumpulan Riset Akuntansi, 2026)
School canteen levies are a form of levy imposed on canteen operators as compensation for the use of school facilities or government-owned land. These levies aim to optimize the utilization of regional assets and improve the overall quality of educational services. This study aims to analyze canteen levy policies in Malang City, considering legal, economic, and social aspects. Therefore, the results of this study are expected to provide more adaptive policy recommendations that support the sustainability of canteen businesses without neglecting their contribution to regional revenue. In analyzing canteen levies, calculations were conducted, where the appropriateness of the tariff was measured based on the cost ratio, which was conducted by analyzing the development of costs (operations, maintenance, and capital/investment) and the provision of facilities and infrastructure. To ensure equitable distribution of regional asset quality, local governments provided a simultaneous subsidy of 50% or 30% to compensate for this, depending on the region's financial capacity. However, this was done by considering the conditions of each canteen, considering the varying amounts of the levy burden. The estimated amount of the levy burden is as follows: 80% of canteens in good condition, 60% of canteens in light damage, and 40% of canteens in severe damage.